A gestão de mudanças na perícia criminal federal: a implementação dos indicadores de complexidade - Pereira, Núbia Fernanda Gomes (2013)
The purpose of this research was to investigate how change management have been applied in the Forensic Branch of the Brazilian Federal Police, as part of a broader field of study related to organizational changes. To determine which analytical categories were crucial to better understand this change process, a comprehensive review of published articles in this field was undertaken, leading to an investigation of three different themes. The first goal of this research was content of change, to determine the exact nature of the transformation proposed. Next, it was evaluated the change implementation process utilized and, finally, in what type of context was this change implemented. More specifically, this qualitative project attempted to assess the change management process occurred during the implementation of complexity indicators in the Forensic Branch of the Brazilian Federal Police, in light of the model proposed by John P. Kotter for the effective implementation of change in organizations, considering their interaction with the organizational context. Data was obtained through semistructured interviews with those responsible for spearheading the process, including management leaders and Directors of the Forensics Branch. Additional data was gathered through the study of organizational documents and direct observation. The results indicated significant competitive factors related to the three fields studied that prevented the achievement of the expected goals, including: a) the proposed change is a kind of performance evaluation, which is a contentious issue that raises many discussions, and, therefore, had very low acceptance; b) unfavorable organizational context, as the Forensics Branch is currently a part of a police organization with a strong punitive and discipline culture; c) process change management was mishandled, according to the theoretical model for the effective implementation of changes in the organizations proposed by Kotter (1995, 1997).